TWO NEW SPECIES OF SPHAERULINA FROM INDIA - ALAKA PANDE; V.G. RAO (Research Center for Biology, 1998)
Two new species of the genus Sphaerulina (Ascomycetes-Dothideales) collected from India are described and illustrated here.